UPAYA PENGEMBANGAN TOTAL QUALITY MANAGEMENT PADA MASYARAKAT PELAKU BISNIS (STUDI KOMPARATIF MANAJEMEN KONVENSIONAL DAN SYARIAH) - Wali Saputra (Lembaga penelitian dan pengabdian kepada masyrakat, 2014)
Total Quality Management (TQM) is an attempt by the company to provide satisfaction to the customers . The concept of quality (quality) for service and non- service basically includes a variety of things that are focused on the customer. A product is created, designed, manufactured and services provided to meet the desires and needs of the customer. Because it is said to be a quality product if it can be exploited, used, consumed in line with expectations, desires, and needs of the customer. Customer satisfaction is very influential on the survival of a company. Considering there is a fundamental difference between the philosophies of quality in the conventional management with quality standards in the management of deep Sharia assesment requires in order to avoid confusion . While there are some principles that the conventional concept of quality management in accordance with the principles of Islamic teachings. Quality standards in the management of Islam based on universal values and timeless as contained in the Qur'an and Sunnah are the main foundation for the way of life of Muslims . Disregard for the core values that exist in the Qur'an and Sunnah will lead to a breakdown in human life . Therefore, the affirmation of the core values that exist in the Qur'an and Sunnah should be the cornerstone of management of sharia. In concept , the sharia management associated with a variety of variables that affect the management of activities within and outside the organization , and the relationship of individual behavior to social factors that influence . Therefore , management sharia regarding various aspects of human life in all areas . sharia value system becomes a principle in every step of human motion , both individually and society , whether in small or large organizations . Therefore, monotheism became the basis for sharia -based institutions in regulating and moral control in organizational life . Second, sincerity can enhance pillars of Tawheed , because without sincerity is not Tawheed has value and meaning. Tawheed without sincerity is the management of non- Muslim life quality. Third,the balance (tawazun). Balance in the various activities of life can give birth to harmony. Fourth, is the creative (work) and innovative. Working as a man who can carry out the principles of worship and mission of the caliph. Fifth, the working principles of trust and transparency as a form of honesty should be the foundation should not be abandoned. Furthermore, the principle of preparation (planning) has an important role in the activity. For all that has been done to enable the evaluation of the need for continuous improvement . Sharia -based management has a vision far ahead is not restricted to a limited time period but for an indefinite period. Because accountability not only in the sight of men , but before God Almighty